Repeat patterns : a manual for designers, artists, and architects - Phillips, Peter; Bunce, Gillian (New York, NY : Thames and Hudson, 1993)
Repeat patterns have been used in ornament, decoration and design since the beginning of civilization. Their use not only links cultures across the globe, but also forms a bridge between the natural and the manmade worlds. This remarkable volume is the key to understanding the most basic and versatile creative tool of all - a design composed of one or more motifs, multiplied and arranged in orderly sequence. Combining mathematical analysis with advanced computer.
technology, the authors present their findings with a brilliant simplicity that can be followed by everyone. They explain the construction principles of each pattern type, as well as the effects of gradation, scale, texture and optical illusions. French Art Deco, Neolithic vase decoration, Celtic stone cross carving, North American Indian beadwork, medieval Italian silk, Persian manuscript illuminations, Chinese cloisonne - the structures of these and many other patterns.
are revealed. While techniques are ideal for use with computers, the book also contains construction by traditional hand methods. The result is utterly indispensable for designers, artists and architects. It will also be a vital learning resource at all levels; and it has a huge range of practical applications in fabric and fashion design, graphics, packaging and advertising, ceramics and tiles, wall and floor coverings, and other media.
Includes bibliographical references (pages 191-192).
Keywords: Repetitive patterns (Decorative arts)